Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1638/2011-0202.1
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective and Prospective Study of Megaesophagus in the Parma Wallaby (Macropus parma) at the San Diego Zoo, California, USA

Abstract: At the San Diego Zoo (California, USA), 22 cases of megaesophagus were diagnosed in the parma wallaby (Macropus parma); a prevalence of 21.1%. Parma wallabies often have no clinical signs until severe and chronic dilation of the esophagus is present. Clinical signs of advanced disease include weight loss, swelling of the cervical region, regurgitation without reswallowing of ingesta, short flight distance, depression, collapse, dyspnea, and sudden death. Retrospective and prospective studies at the San Diego Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Retrospective studies, including those that make use of zoo records, are an indispensable tool in the identification of disease patterns [ 3 , 31 , 32 , 33 ], and can also be used to evaluate the efficacy of interventions, such as modifications to husbandry practices, aimed at reducing the incidence of a disease [ 34 , 35 ]. Studies such as this provide important information from which zoological institutions can make management decisions that may reduce the risk of MPPD and help to conserve the health and welfare of macropods in captivity.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies, including those that make use of zoo records, are an indispensable tool in the identification of disease patterns [ 3 , 31 , 32 , 33 ], and can also be used to evaluate the efficacy of interventions, such as modifications to husbandry practices, aimed at reducing the incidence of a disease [ 34 , 35 ]. Studies such as this provide important information from which zoological institutions can make management decisions that may reduce the risk of MPPD and help to conserve the health and welfare of macropods in captivity.…”
Section: Discussionmentioning
confidence: 99%
“…No underlying cause of the megaoesophagus was identified. In a recent review by Burgdorf‐Moisuk and colleagues (2012), it was reported that megaoesophagus in parma wallabies is common and that clinical signs of advanced disease include weight loss, collapse, dyspnoea and sudden death; no underlying aetiology was established and the authors speculated about unrecognised environmental or nutritional causes.…”
Section: Miscellaneous Speciesmentioning
confidence: 99%
“…Wallaby medicine is a developing branch of veterinary medicine worldwide [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Among the diseases described in the literature, parasitic infestations [ 12 ], bacterial diseases of the oral cavity [ 13 ], and cardiomyopathies can be mentioned [ 8 ].…”
Section: Introductionmentioning
confidence: 99%